2017
DOI: 10.2196/jmir.7513
|View full text |Cite
|
Sign up to set email alerts
|

Using Digital Technologies in Clinical HIV Research: Real-World Applications and Considerations for Future Work

Abstract: BackgroundDigital technologies, especially if used in novel ways, provide a number of potential advantages to clinical research in trials related to human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) and may greatly facilitate operations as well as data collection and analysis. These technologies may even allow answering questions that are not answerable with older technologies. However, they come with a variety of potential concerns for both the participants and the trial sponso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Participants in our study suggested more entertaining technological approaches to stay relevant to their demographic, such as the use of gaming and social networking applications to collect sexual risk information. Most social networking sites are not private or secure, and due consideration would need to be given to balance the need for privacy and security of participant data with the preference for young people to interact through accessible technology [57].…”
Section: Discussionmentioning
confidence: 99%
“…Participants in our study suggested more entertaining technological approaches to stay relevant to their demographic, such as the use of gaming and social networking applications to collect sexual risk information. Most social networking sites are not private or secure, and due consideration would need to be given to balance the need for privacy and security of participant data with the preference for young people to interact through accessible technology [57].…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory authorities may be reluctant to allow the use of new technologies in clinical trials due to concerns regarding data security [ 5 ]. However, these problems will be overcome, and new technologies will be implemented in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic data capture (EDC) is defined as the collection of clinical trial data on paper (e.g., case report forms, patient diaries, and patient reports) into electronic form. EDC using mobile digital technologies enables clinical trials to be performed more rapidly and at a lower cost [ 4 5 ]. Real time direct data capture in clinical trials enhances EDC by increasing the data accuracy and reducing costs [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technological revolution has provided opportunities for integrating digital resources into clinical research activities [ 1 , 24 , 26 ]. Some studies have incorporated electronic technologies into research using internet and mobile services for clinical research recruitment and retention, electronic consent processes, internet-based interventions, and for web-based data collection and study result dissemination [ 26 ].…”
Section: Introductionmentioning
confidence: 99%